Recipes for Change validation report: Rwandan bananas with beans and split green peas - Norman, James (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The main climate risks to beans cultivation in Rwanda are: (i) extreme precipitation levels, primarily in the northern and western regions (Ruhengeri, Gisenyi, Gikongoro and Byumba) where abundant rainfall can cause erosion, flooding and landslides, (ii) Biotic stresses, primarily plant diseases and pests and (iii) post-harvest losses resulting from increasingly favourable environments for damaging micro-organisms and insects. The main adaptation measures for managing the expected impacts of climate change on bean cultivation include: (i) continued development and adoption of both climate resilient and higher-nutrition bean varieties, (ii) integration of flood and land management practices at the catchment and farm-scale and (iii) improved provision of drying, threshing and storage facilities. CCAFS validates the climate threats and solutions highlighted in the IFAD statements below (which refer to maize as well as beans). CCAFS also identifies drought stress as a possible climatic hazard to bean cultivation. One caveat is that CCAFS research, using modelling approaches shown in Figure 2, indicates that average growing conditions, including average precipitation levels, are conducive to the continued and, in some areas, improved viability of bean cultivation. This does not preclude, however, the possibility of continued or increased variability in precipitation and elevated evapotranspiration combining to enhance the prevalence or severity of droughts during some seasons in future years. But it remains unclear if such an effect would prevail in the situation of generally increasing annual average levels of rainfall. Comparably, if the impact of temperature extremes remains moderate and the risks of biotic stresses can be mitigated, the analysis from climatic niche modeling suggests the continued viability of bean growth in a changing climate. Less can be said from the scientific point of view about post-harvest risks and solutions in the harvesting, storage and transport of beans, since little research has been done on these issues. However, any reductions of post-harvest losses will have both adaptation and mitigation benefits.